Implementation of the Internet of Things in Centrifuge Calibrators - Kuspranoto, Abdul Haris; Alfatih, Muhammad Fa'iz; Yudono, Muchtar Ali Setyo (Universitas Nusa Putra, 2024)
The implementation of Internet of Things (IoT) technology in centrifuge calibrators brings innovation by enhancing accuracy and efficiency in medical device calibration. This research develops an IoT-based centrifuge calibrator capable of storing calibration data digitally and providing real-time access, using the E18-D80NK sensor for rotational motion detection, which is more cost-effective than conventional laser modules. Measurement results demonstrate high accuracy across various RPM settings (1000, 1500, 2000, 2500, and 3000 RPM), with minimal error and stability within acceptable tolerance limits. The key advantage of IoT implementation lies in efficient calibration data management, enabling real-time access and integration with other systems for effective analysis and monitoring of calibration outcomes. Overall, IoT technology in centrifuge calibration not only enhances healthcare service quality with reliable results but also supports efficient and transparent equipment management in medical settings, offering long-term benefits to healthcare facilities and patients.